2017
DOI: 10.1042/bst20160132
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the hepatocyte growth factor/Met pathway in cancer

Abstract: Hepatocyte growth factor (HGF)-induced activation of its cell surface receptor, the Met tyrosine kinase, drives mitogenesis, motogenesis and morphogenesis in a wide spectrum of target cell types and embryologic, developmental and homeostatic contexts. Typical paracrine HGF/Met signaling is regulated by HGF activation at target cell surfaces, HGF binding-induced receptor activation, internalization and degradation. Despite these controls, HGF/Met signaling contributes to oncogenesis, tumor angiogenesis and inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 109 publications
1
41
0
Order By: Relevance
“…Most importantly, the molecular differences create opportunities for various treatment modalities toward a more individualized therapy approach. For example, MET pathway-targeted anticancer therapies may be more effective in PDACs of the immune-escape subtype, to additionally target EMT-like tumor budding, as mutations in the receptor tyrosine kinases MET and ERBB4 were more frequent in the immuneescape cases (38,39). In a recent study, dual MET and ERBB inhibition was shown to overcome intratumor plasticity in osimertinib-resistant advanced non-small cell lung cancer (40).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the molecular differences create opportunities for various treatment modalities toward a more individualized therapy approach. For example, MET pathway-targeted anticancer therapies may be more effective in PDACs of the immune-escape subtype, to additionally target EMT-like tumor budding, as mutations in the receptor tyrosine kinases MET and ERBB4 were more frequent in the immuneescape cases (38,39). In a recent study, dual MET and ERBB inhibition was shown to overcome intratumor plasticity in osimertinib-resistant advanced non-small cell lung cancer (40).…”
Section: Discussionmentioning
confidence: 99%
“…Limiting neutrophil recruitment by blocking cMET promotes the efficacy of adoptive T cell transfer and checkpoint therapy in murine melanoma ( 196 ). Antagonists of the HGF/cMET pathway have been developed and are being tested in multiple types of human cancer ( 197 ).…”
Section: Targeting Neutrophil Activity In Cancer Therapymentioning
confidence: 99%
“…Concerning HGF/c-MET specific drugs, two major classes are described: the small molecules tyrosine kinase inhibitors (TKIs), whose mechanism of action is mainly intracellular and the human monoclonal antibodies that recognize extracellular components. A comprehensive review of these drugs was performed by De Silva et al (2017) [ 127 ]. Monoclonal antibodies targeting HGF/c-MET pathways have been evaluated in clinical trials and are able to recognize the HGF or the c-MET extracellular domains, ultimately disturbing HGF/c-MET interaction and signaling.…”
Section: Strategies To Target Hgf/cmet–ecm Interactionsmentioning
confidence: 99%